(untitled) (Fiep Bulletin - online, 2013)
This research, of qualitative character, was performed with 35 elderly participants in the Project PELC Health Life: living and coexisting at “Casa do Caminho Simão Pedro” in Manaus City, and aimed acting effectively in aging process calling attention to socialmotricity importance to social reintegration of elderly people with Hansen sequels. This program was develop twice a week and consisted in physical activities, dances, recreations, movies, walks, art workshops and lectures, easily accepted to group and involved everyone. We verified a relevant improvement in general state of the group, self-esteem, in affective considerations, autonomy and sociability. Improving the psycho and social of elderly, we are benefiting their wellness and promoting their independence to perform daily activities and society reintegration.